2014
DOI: 10.1007/s10616-014-9780-6
|View full text |Cite
|
Sign up to set email alerts
|

Health risk assessments of lithium titanate nanoparticles in rat liver cell model for its safe applications in nanopharmacology and nanomedicine

Abstract: Due to their high chemical stability, lithium titanate (Li2TiO3) nanoparticles (LTT NPs) now are projected to be transferred into different nanotechnology areas like nano pharmacology and nano medicine. With the increased applications of LTT NPs for numerous purposes, the concerns about their potential human toxicity effects and their environmental impact are also increased. However, toxicity data for LTT NPs related to human health are very limited. Therefore we aimed to investigate toxicity potentials of var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…After that 100 lL supernatant and 100 lL of reaction mixture were transferred to a fresh 96-well plate and incubated for 30 min at room temperature. Finally, the absorbance of the cultures was analyzed at 490 nm using a microplate reader (Turkez et al 2016).…”
Section: Ldh Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…After that 100 lL supernatant and 100 lL of reaction mixture were transferred to a fresh 96-well plate and incubated for 30 min at room temperature. Finally, the absorbance of the cultures was analyzed at 490 nm using a microplate reader (Turkez et al 2016).…”
Section: Ldh Assaymentioning
confidence: 99%
“…To extract the NR from the HPAEpiC cells, a mixture of acetic acid (1 %) and ethanol (50 %) were added to the cell cultures and incubated at room temperature for 30 min. Finally, the microplate reader (Bio-Tek Instruments, USA) was used to analyze optical density of each sample at 540 nm (Turkez et al 2016).…”
Section: Neutral Red Assaymentioning
confidence: 99%
“…8-hydroxy-2′-deoxyguanosine (8-OH-dG) assay kits were purchased from Cayman Chemical (Ann Arbor, MI, USA) for determining 8-OH-dG levels in cultures. All procedures were carried out in accordance with the provider's manual (Turkez et al, 2016b). In genotoxicity assays, mitomycin-C (10 -7 M) was used as control (+).…”
Section: Testing Cytotoxicity Genotoxicity and Oxidative Alterationsmentioning
confidence: 99%
“…It is believed that Xiyin liangxue decoction is more effective in treating IgA nephropathy rats than western medicine, although it takes a longer time, but with fewer side effects [5] . Turkez examined the potential toxicity of various concentrations (0-1000 ppm) of LTT NP (<100 nm) in cultured primary rat kidney cells through 3-(4,5-dimethylthiazole-2-Base) 2,5-diphenyltetrazolium bromide (MTT) determination and lactate dehydrogenase (LDH) release to detect cell viability and found that all aspects of kidney disease rats fed Xiyin liangxue decoction are better [6] . Shinoda pointed out that the key to treating IgA nephropathy rats is to reduce side effects and strengthen prognosis management.…”
mentioning
confidence: 99%